The relationship between job stress and the perception of patient safety culture among Palestinian hospital nurses - Loai M. Zabin; Jamal Qaddumi; Sajed Faisal Ghawadra (BMC Nursing)
Abstract Background Patient safety is a global concern, with high rates of medical errors reported annually. Understanding the relationship between nurses’ job stress and patient safety culture (PSC) is crucial. Despite their pivotal role in healthcare, nurses face stress due to demanding job roles and the challenging healthcare system in Palestine. This study aims to explore the relationship between nurses’ job stress and PSC in Palestinian hospitals, identifying predictors that impact PSC to enhance healthcare outcomes and support healthcare professionals. Methods This study employed a quantitative cross-sectional approach. Data collection took place from June to September 2023. The study utilized self-report surveys, including the Hospital Survey of Patient Safety Culture (HSOPSC) and the Nursing Stress Scale (NSS), administered to 355 nurses working in 16 North West Bank hospitals in Palestine. The data collected were analyzed via descriptive and inferential analysis. Results Overall, 47% of the nurses reported having positive PSC. The areas with the most positive perception were “teamwork” and “organizational learning-continuous improvement”, with mean percentages of positive responses of 63.1% and 55.8%, respectively. Conversely, the composites with the lowest positive response scores included “Response to Error” and “Staffing and Work Pace”, with mean percentages of positive responses of 30.9% and 34.8%, respectively. Furthermore, the most common sources of job stress perceived by nurses were “workload” and “death and dying”, with mean scores of 1.42 and 1.20, respectively. However, the lowest-scoring sources of stress were in the subscales “Uncertainty concerning treatment” and “Inadequate preparation”, with mean scores of 1.02 and 1.06, respectively. Statistical tests revealed that six factors were significantly associated with the perception of PSC. Among these factors, income, hospital type, activities to improve PSC, patient safety ratings of work areas, and weekly night shifts emerged as predictors of PSC. Additional tests revealed nine factors significantly associated with job stress. Among these factors, gender, educational level, engagement in stress relief activities, participation in PSC improvement activities, and patient safety ratings emerged as predictors of job stress. Moreover, the study revealed negative correlations between job stress and PSC. Conclusion This study identified the need for tailored policies and interventions that address nurses’ specific stressors to enhance PSC within hospital settings. Moreover, the study shed light on the unique challenges faced by nurses in Palestine, such as limited resources, unemployment concerns, staffing, and transportation issues, which further exacerbated job stress levels and potentially compromised patient safety. Understanding these contextual factors is crucial for developing targeted interventions and support systems that prioritize the holistic well-being of nurses and the quality of patient care delivery.